Knowledge and Practices on Periodontal Health among Adults, Misungwi, Tanzania - John Michael Nyorobi; Lorna Celia Carneiro; Msafiri Nicodemus Kabulwa (Hindawi Limited, 2018)
The level of knowledge and practices on periodontal health of 388 adults in Misungwi District, Tanzania, was assessed. Analysis included frequency distributions and the chi-square test at a p value of 0.05. Many more participants were males (n=197; 50.8%) and of younger age group (n=215; 55.4%) and having seven years of education (n=257; 66.2%). Higher number of participants reported owning a mobile phone (n=289; 74.5%) and a radio (n=298; 76.8%), while few (n=45; 11.6%) had their houses connected to electricity. Study participants who were males (n=101; 51.3%), had more than seven years of schooling (n=67; 72.3%), who owned a mobile phone (n=143; 49%), owned a radio (n=144; 48.3%), and resided in houses having electricity (n=37; 82.2%) were statistically significantly more knowledgeable on periodontal health when compared to their counterparts. A statistical significant difference was seen in oral health practices conducive to periodontal health among those who were males (n=133; 67.0%), having more than seven years of education (n=78; 83.0%), owning a mobile phone (n=189; 65.4%), owning a radio (n=195; 65.4%), and residing in house having electricity (n=35; 77.8%). This study observed that participants who were males, owned a mobile phone, owned a radio, resided in houses having electricity, and having more than seven years of education were more knowledgeable and had more conducive oral health practices on periodontal health.